2021
DOI: 10.1007/s13311-021-01096-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural Neuroimaging Findings Related to Adult Non-CNS Cancer and Treatment: Review, Integration, and Implications for Treatment of Cognitive Dysfunction

Abstract: Cancer-and treatment-related cognitive dysfunction (CRCD) is a common challenge faced by patients diagnosed with noncentral nervous system (CNS) cancer. It has become increasingly recognized that multiple factors likely play a role in these symptoms, including the cancer disease process, systemic treatments (e.g., chemotherapy and endocrine therapies), and risk factors that may predispose an individual to both cancer and cognitive dysfunction. As the field has evolved, advanced neuroimaging techniques have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 107 publications
0
11
0
1
Order By: Relevance
“…Although the mechanism of the effect of acupuncture in the treatment of this disease is not clear, some studies have shown that acupuncture and its related therapies (such as auricular acupuncture and warm acupuncture) have great potential as an adjuvant therapy to alleviate CRF in patients and improve the quality of survival of patients, and the clinical studies of acupuncture and its related therapies in recent years are summarized, analyzed, and summarized as follows. A randomized double-blind controlled trial was conducted by [ 12 ], which included 28 patients with CRF of lung cancer, with acupoints selected as 45 min/time, 2 times/week, and continued treatment for 4 weeks with a 2-week follow-up, while the sham acupuncture group took the same acupoints but without needles into the skin [ 13 ].…”
Section: Related Workmentioning
confidence: 99%
“…Although the mechanism of the effect of acupuncture in the treatment of this disease is not clear, some studies have shown that acupuncture and its related therapies (such as auricular acupuncture and warm acupuncture) have great potential as an adjuvant therapy to alleviate CRF in patients and improve the quality of survival of patients, and the clinical studies of acupuncture and its related therapies in recent years are summarized, analyzed, and summarized as follows. A randomized double-blind controlled trial was conducted by [ 12 ], which included 28 patients with CRF of lung cancer, with acupoints selected as 45 min/time, 2 times/week, and continued treatment for 4 weeks with a 2-week follow-up, while the sham acupuncture group took the same acupoints but without needles into the skin [ 13 ].…”
Section: Related Workmentioning
confidence: 99%
“…HT exposure over the recommended 5-10 years has the potential to interact with other risks for cognitive decline (e.g., medical comorbidities, cognitive aging, dementia). Furthermore, while we only examined women who did not receive chemotherapy, HT and chemotherapy effects may be additive, especially as similar frontal and temporal regions appear vulnerable to effects of both types of treatment [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…While extensively used to examine structural and functional brain changes after breast cancer chemotherapy [26][27][28][29][30], neuroimaging has not been widely applied to examine the impact of HT. Lower hippocampal volume and resting hippocampal-prefrontal functional connectivity have been reported in women with breast cancer taking tamoxifen [31,32], and Hurria and colleagues found metabolic changes on FDG-PET in post-menopausal women with breast cancer taking an aromatase inhibitor, notably in regions relevant to aging [33].…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging studies provide information on changes in brain structure and patterns of neural activities that individuals use when they engage in various cognitive processes that underlie tasks of daily life [66][67][68]. The brain region most associated with executive functions and inhibitory control processes is the prefrontal cortex (PFC) [69,70].…”
Section: Potential Mechanisms Associated With Differences In Cognitiv...mentioning
confidence: 99%